Strategies of police and analytical support for financial crime prevention in a context of global geopolitical crisis. Guidelines for ensuring financial security in Ukraine - Solomiia Vasyuk; Volodymyr Panchenko; Oksana Panchenko; Nataliia Svyrydiuk; Mykola Kuzminov (Clío)
Russian invasion of Ukraine has increased the need to discuss sound strategies for preventing financial crimes, in the context of the global geopolitical crisis. Therefore, the aim of the article was to analyze various strategies for the prevention of financial crimes in two particular but connected contexts: on the one hand, the international scenario and, on the other hand, the Ukrainian reality, where the guidelines for ensuring financial security are defined, in a country going through a war that affects its national sovereignty, resulting from the invasion of the Russian federation. Methodologically, different cognitive tools were combined, such as: critical geopolitics, documentary research and discourse analysis. The results obtained show how cooperation between the public and private sectors is essential to establish a solid international system of prevention and police response to financial crimes and, moreover, to promote a culture of security and responsibility at all levels of reality. It is concluded that preventing financial crime in the context of global geopolitical crises requires a multifaceted approach that combines international cooperation, data analysis, education, critical thinking, and a deep understanding of geopolitical dynamics.